Leptomeningeal metastasis: Clinical experience of 519 cases. (March 2016) - Hyun, Jae-Won; Jeong, In Hye; Joung, AeRan; Cho, Hyo Jin; Kim, Su-Hyun; Kim, Ho Jin
Abstract: Background: Diagnosis of leptomeningeal metastasis (LM) has become increasingly common because of enhanced detection via routine use of magnetic resonance imaging (MRI) and longer survival of patients by better systemic control. We investigated clinical features and analyzed potential prognostic factors in a large cohort of patients with LM. Methods: The clinical features of LM developing from systemic cancers were analyzed retrospectively in patients at the National Cancer Center during 2005–2014. Results: A total of 519 patients were enrolled; 497 had solid, 19 had hematopoietic tumors and 3 had tumors of unknown etiology. Among the solid tumors, the most common primary tumor was lung cancer (334 patients), followed by breast cancer (96) and gastrointestinal cancer (39). Median age at onset was 56 years, and the median Karnofsky performance status (KPS) was 60. Thirty-five percent of patients were diagnosed by MRI alone, 22% by cerebrospinal fluid (CSF) cytology alone, and 42% by both. Treatment included chemotherapy alone in 45%, radiation therapy alone in 10%, and both in 17%; 28% received supportive care alone. Median overall survival was 3 months. KPS ≥70, CSF protein level ≤50 mg/dl at the diagnosis of LM, and active treatment were associated independently with longer overall survival. Upon subgroup analysis of lung cancer patients, non-small cell lung cancer was a favorable prognostic factor for overall survival. Conclusions: Despite improved diagnosis via MRI and vigorous therapy, most patients with LM had poor outcomes. However, patients with a high KPS or normal CSF protein levels had favorable prognoses upon active treatment. Highlights: We consecutively enrolled 519 patients with leptomeningeal metastasis (LM) from various tumors diagnosed over 10 years. We investigated clinical features and analyzed potential prognostic factors in a large cohort of patients with LM. Despite improved diagnosis via magnetic resonance imaging and vigorous therapy, most patients had poor outcomes. Patients with a high Karnofsky performance status or normal cerebrospinal fluid protein levels at the time of LM diagnosis had favorable prognoses upon active treatment.